2017
DOI: 10.1093/jxb/erx418
|View full text |Cite|
|
Sign up to set email alerts
|

Arabidopsis MKK10-MPK6 mediates red-light-regulated opening of seedling cotyledons through phosphorylation of PIF3

Abstract: The kinases responsible for phosphorylation of phytochrome-interacting factors (PIFs) in plants undergoing photomorphogenesis are largely unknown. We show that the MKK10-MPK6 cascade regulates red light-induced photomorphogenesis through phosphorylation of PIF3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…Additional protein kinases have been implicated in PIF phosphorylation and subsequent proteasome-mediated degradation including BIN2, CK2, and MPK6 (refs. 73,7678 ) (reviewed in ref. 41 ).…”
Section: Phytochrome Signaling Elicited Through Light-activated Intermentioning
confidence: 99%
“…Additional protein kinases have been implicated in PIF phosphorylation and subsequent proteasome-mediated degradation including BIN2, CK2, and MPK6 (refs. 73,7678 ) (reviewed in ref. 41 ).…”
Section: Phytochrome Signaling Elicited Through Light-activated Intermentioning
confidence: 99%
“…Upon exposure to light, PIFs are phosphorylated and degraded. Recently, Xin et al reported the involvement of Arabidopsis MKK10-MPK6 module in regulating cotyledon opening upon red light exposure (Xin et al, 2018 ). Moreover, MPK6 interacts with and phosphorylates PIF3 leading to its degradation.…”
Section: Developmentmentioning
confidence: 99%
“…Moreover, MPK6 interacts with and phosphorylates PIF3 leading to its degradation. Collectively, the results of Xin et al suggest that a module composed of MKK10-MPK6-PIF3 regulates seedling photomorphogenesis in response to red light (Xin et al, 2018 ).…”
Section: Developmentmentioning
confidence: 99%
“…BIN2 has also been shown to regulate the phosphorylation and transcriptional activity of PIF4 in diurnal conditions (14). Recently, there is evidence showing that phytochromes, Photoregulatory Protein Kinases (PPKs), and MPK6 can also phosphorylate PIF3 proteins (18)(19)(20). In contrast to the extensive studies of PIF protein phosphorylation, dephosphorylation of PIF proteins is poorly understood.…”
mentioning
confidence: 99%